2013
DOI: 10.1097/rct.0b013e318287efa0
|View full text |Cite
|
Sign up to set email alerts
|

Achilles Tendinopathy and Partial Tear Diagnosis Using Dual-Energy Computed Tomography Collagen Material Decomposition Application

Abstract: Computed tomographic (CT) scans of the ankle and foot are frequently obtained with in-patients with hind foot and ankle pain to identify fractures, arthritis, and bone lesions. Soft tissue detail is limited, however. Dual-energy CT provides additional information on soft tissue structures, including tendons, with no additional radiation dose to the patient. We present a case of an Achilles tendon tear visualized on DECT, which was subsequently confirmed with magnetic resonance imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Tendinopathy also has been diagnosed in the Achilles tendon. 33 Similar positive results have been reported in large ligamentous structures, such as the anterior cruciate ligament, and initial case reports also show positive results in the diagnosis of complete tears of small ligamentous structures in the extremities, such as plantar plate injury of the foot. 34 In an animal study, Fickert and colleagues 35 compared the diagnostic accuracy of DECT and MR imaging in the detection of arthroscopically induced total and partial tears of the anterior cruciate ligament (ACL) in 20 porcine hind legs.…”
Section: Tendons and Ligamentssupporting
confidence: 51%
“…Tendinopathy also has been diagnosed in the Achilles tendon. 33 Similar positive results have been reported in large ligamentous structures, such as the anterior cruciate ligament, and initial case reports also show positive results in the diagnosis of complete tears of small ligamentous structures in the extremities, such as plantar plate injury of the foot. 34 In an animal study, Fickert and colleagues 35 compared the diagnostic accuracy of DECT and MR imaging in the detection of arthroscopically induced total and partial tears of the anterior cruciate ligament (ACL) in 20 porcine hind legs.…”
Section: Tendons and Ligamentssupporting
confidence: 51%
“…Peltola et al reported high SE (79%) and SP (100%) when using it to detect anterior cruciate ligament tears [27]. Mallinson et al diagnosed Achilles tendinopathy with a technique similar to the one we used [12]. Kumar et al detected and quantified myocardial fibrosis [20].…”
Section: Discussionmentioning
confidence: 99%
“…Special postprocessing tools allow detection of bone marrow edema using the so-called virtual non-calcium technique [11]. When a three-material decomposition algorithm is applied, DECT also allows visualization of collagenous structures such as tendons and ligaments [12, 13]. In this study, we applied this technique to the vertebral disk.…”
Section: Introductionmentioning
confidence: 99%
“…8,37 The disruption of larger collagen-based structures such as the triceps tendon and cruciate ligaments was demonstrated. 38,39 In theory, if the collagen algorithm is optimized, even partial tears, which are also difficult to identify on MRI, could become more conspicuous.…”
Section: Collagen Imagesmentioning
confidence: 99%